(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2016)
Each and every five year plan, the priority for the nation has been its economic growth, education for all and financial inclusion for the vast population of the country. While India has made some noteworthy progress in the past six and half decades and more, but on the aspect of financial inclusion, progress has not been satisfactory. According to census 2011, out of 24.67 crore households in India, only about 14.48 crore (58.70 %) households had access to banking services. Further, of the 16.78 crore rural households, only about 9.14 crore (54.46 %) households were availing of banking services.” “The World Bank Findex Survey (2012) points out that only about 35% of Indian adults had access to a formal bank account and a meager 8% borrowed formally in the last 12 months,” The question now is do we can either continue with our traditional ways of ensuring financial inclusion or look at new methods and opportunities that is available to us because of technology? India has made rapid strides in technology and it is important to now look at financial inclusion through the prism of the digital economy. The government of India has taken initiative to digitize services that made available to citizens electronically by improving online infrastructure and by increasing Internet connectivity.